METHOD OF TREATING PLEURAL ABNORMALITY (2015)
The invention relates to a method of treating pleural abnormalities in a subject in need thereof, comprising the steps of: (a) attaching a biodegradable polymeric membrane onto a pleural wound to elicit fibronectin from fibroblasts to cause fibrous adhesion; and (b) securing the membrane with securement products, including sutures, staples, and sealants. The present invention also relates to a biodegradable adhesion membrane used for treating pleural abnormalities, comprising: a biodegradable base material selected from the group consisting of polycaprolactone (PCL), polylactic acid or polylactide (PLA), polyhydroxybutyrate (PHB), poly(ethylene adipate), poly(butylene adipate) (PBA), chitosan, hyaluronic acid, and polyglycolic acid (PGA); wherein the thickness of the membrane is 0.1-1 mm.